Analisa Pengaruh Revitalisasi Pasar Rakyat, Pelatihan Pedagang Dan Kualitas Layanan Pengelolaan Pasar Rakyat Terhadap Omzet Pasar Rakyat - Ibnu Adam; Aswin Naldi Sahim; Widya Nengsih (Journal of Innovative and Creativity, 2025)
Public market is one of the trading facilities that is still the foundation and centre of populist economic activities in Indonesia. In order to realize competitive trading facilities, market revitalization programs aimed to improving the physical and non-physical aspects of the public market, including improvements quality of management services and capacity building. The result is an increase in the number of transactions and omzet traders, which is the basis for the formation omzet of public market. This study aims to analyze the effect of revitalization of public markets, quality of management services and training for traders, as partially and simultaneously on the omzet of public markets. This study was conducted using a descriptive quantitative approach with a questionnaire method using non-random/non-probability sampling. Sampling using the slovin method of 399 traders from 14 public markets that received the Ministry of Trade's public market revitalization program. Research analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) through validity and reliability analysis, as well as analysis of related variables. From the results of the analysis, it was found that the revitalization of the public market had a significant effect on the omzet of 3.442; trader training had no effect on the omzet of 0.254; the quality of market management services had a significant effect on the public market turnover of 3.174; the quality of market management services was a full mediator of the relationship between the revitalization of the public market and omzet of 2.362 and the relationship between trader training and omzet of 3.332.